Predição do desenvolvimento folicular: estudo de reserva ovariana em ciclos de fertilização assistida - Spressão, Meire (2016)
Research on infertility has evolved with continuing studies and technological advances. As assessing the ovarian reserve, the objectives are to predict the chances of response to the induction and select the “optimal” dose for the ovarian hyperstimulation. Among the aspects of clinical history, age is considered a determining factor of fertility. Studies have demonstrated an apparent correlation between the ovarian volume, the antral follicles count and the functional status of the ovaries. The basal serum follicle stimulating hormone concentration has been used as a marker for ovarian insufficiency. The dosage of anti-Müllerian hormone has been used as early and sensitive marker of ovarian reserve. This hormone is strongly associated with antral follicles count. Despite the importance of the ovarian reserve measurement, the best way to correctly evaluate the follicular status remains controversial. Purpose: The main objective is to identify whether the usual methods for assessing ovarian reserve as age, follicle stimulating hormone, ovarian volume and antral follicle count are sufficient to identify the best response to follicle development. The secondary objective is to check that the anti-Mullerian hormone dosage is self-sufficient in the ovarian reserve assessment. Casuistry and Methods: Retrospective cohort study, comprising patients in treatment on Assisted Reproduction at the Institute for Reproductive Medicine, from April 2009 to July 2014. Age, biochemical tests, and ultrasound were assessed. The data were analyzed to predict the follicular development and the relation between themselves using, for statistical analysis, the Statistical Package program for Social Sciences. Results: Of the 293 couples included, 50.2% had infertility for ovarian factor. The average age was 34.7 years. Considering the age as the main variable, and a significant negative correlation with the volume of both ovaries was observed (right ovary cc=- 0.21; equerdo cc=-0.22; both p<0.0001) with antral follicle count (right ovary cc=-0.38; left cc=-0.47; both p<0.0001). Considering antral follicle count as a main variable, a significant positive correlation was observed with total recruited oocytes (right ovary cc = 0.73; left cc = 0.72, total antral follicles cc = 0.77; all p<0.0001 ). When correlated with antral follicle count greater than 18 mm follicles recruited, it is observed that with a cutoff of 12 antral follicles has a positive predictive value of 99% and the area under the ROC curve of 0.76. According to the number of antral follicles, three groups were separated: fewer than six, six to 15 and more than 15, it is observed that the first subgroup showed older age than the other groups (P<0.0001), fewer follicles recruited to the other groups (P<0.0001). Conclusions: We concluded in our study that age and antral follicle count are effective predictors of ovarian response in Assisted Reproduction cycles. The dosage of follicle stimulating hormone and the ovarian volume are not specific markers for ovarian response to ovulation induction protocols. The dosage of anti-Mullerian hormone appears to be an excellent marker of ovarian reserve and it stands out to the need for further complementary studies.